Smart Partnership - The Star, Jade Chan (2011)
SUBANG jaya Municipal Council (MPSJ) president Datuk Adnan Md Ikshan believes there is a lot potential for the smart partnership programme between the council and Universiti Putra Malaysia (UPM), which would benefit both parties.